Peripheral Motor and Sensory Nerve Conduction following Transplantation of Undifferentiated Autologous Adipose Tissue–Derived Stem Cells in a Biodegradable U.S. Food and Drug Administration–Approved Nerve Conduit. Issue 1 (July 2016) - Klein, Silvan M.; Vykoukal, Jody; Li, De-Pei; Pan, Hui-Lin; Zeitler, Katharina; Alt, Eckhard; Geis, Sebastian; Felthaus, Oliver; Prantl, Lukas
Abstract : Background: Conduits preseeded with either Schwann cells or stem cells differentiated into Schwann cells demonstrated promising results for the outcome of nerve regeneration in nerve defects. Methods: The concept of this trial combines nerve repair by means of a commercially available nerve guidance conduit and preseeding with autologous, undifferentiated, adipose tissue-derived stem cells. Adipose tissue-derived stem cells were harvested from rats and subsequently seeded onto a U.S. Food and Drug Administration–approved type I collagen conduit. Sciatic nerve gaps 10 mm in length were created, and nerve repair was performed by the transplantation of either conduits preseeded with autologous adipose tissue-derived stem cells or acellular (control group) conduits. After 6 months, the motor and sensory nerve conduction velocity were assessed. Nerves were removed and examined by hematoxylin and eosin, van Gieson, and immunohistochemistry (S100 protein) staining for the quality of axonal regeneration. Results: Nerve gaps treated with adipose tissue-derived stem cells showed superior nerve regeneration, reflected by higher motor and sensory nerve conduction velocity values. The motor and sensory nerve conduction velocity were significantly greater in nerves treated with conduits preseeded with adipose tissue-derived stem cells than in nerves treated with conduits alone ( p < 0.05). Increased S100 immunoreactivity was detected for the adipose tissue-derived stem cell group. In this group, axon arrangement inside the conduits was more organized. Conclusions: Transplantation of adipose tissue-derived stem cells significantly improves motor and sensory nerve conduction velocity in peripheral nerve gaps. Preseeded conduits showed a more organized axon arrangement inside the conduit in comparison with nerve conduits alone. The approach used here could readily be translated into a clinical therapy. CLINCAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, V.